Pre-rehabilitation scores of functioning measured using the World Health Organization Disability Assessment Schedule in persons with nonspecific low back pain: a scoping review. Issue 4 (19th September 2022) - Wong, Jessica J.; DeSouza, Astrid; Hogg-Johnson, Sheilah; De Groote, Wouter; Varmazyar, Hamid; Mior, Silvano A.; Stern, Paula J.; Southerst, Danielle; Alexopulos, Stephanie; Belchos, Melissa; Lemeunier, Nadège; Nordin, Margareta C.; et al.
Abstract : Knowledge of the pre-rehabilitation generic status of functioning in individuals with low back pain is necessary to understand the clinical utility of rehabilitation care. We conducted a scoping review to describe the pre-rehabilitation functioning status of persons with nonspecific low back pain using the World Health Organization Disability Assessment Schedule (WHODAS)-36 or WHODAS-12. We searched multiple databases from 2010 to 2021 for studies reporting pre-rehabilitation scores using WHODAS in persons with low back pain. Reviewers independently screened articles and extracted data, and we descriptively summarized results by the duration of low back pain (acute/subacute <3 months; chronic ≥3 months), and the WHODAS version. Of 1770 citations screened, eight citations were relevant. Five studies were conducted in Europe, two in America, and one in the African Region (mostly high-income countries). In persons with acute low back pain, the mean WHODAS-36 pre-rehabilitation summary score (complex scoring) was 22.8/100 (SD = 15.4) (one study). In persons with chronic low back pain, the mean WHODAS-36 summary score (complex scoring) ranged from 22.8/100 (SD = 5.7) to 41.5/100 (SD = 13.8) (two studies). For WHODAS-12 in persons with chronic low back pain, the mean summary score was 11.4/48 (SD = 8.7) or 14.4/48 (SD = 9.4) using simple scoring (two studies), and 25.8/100 (SD = 2.2) using complex scoring (one study). No floor or ceiling effects were observed in WHODAS-36 summary scores for chronic low back pain. Our scoping review comprehensively summarizes available studies reporting pre-rehabilitation levels of functioning using WHODAS in persons with low back pain. Persons with low back pain seeking rehabilitation have moderate limitations in functioning, and limitations level tends to be worse with chronic low back pain.